The impact of hunger on indulgent food choices is moderated by healthy eating concerns - Otterbring, Tobias; Folwarczny, Michał; Gasiorowska, Agata (Frontiers in Nutrition, 2024)
Research has shown that hungry individuals are more impulsive, impatient, and prone to make indulgent food choices compared to their satiated counterparts. However, the literature is still mixed, with some studies showing such results while others fail to demonstrate hunger effects on consumers' choice behavior. The current cross-sectional study (N = 461) sought to address these inconsistencies by examining whether the link between hunger and people's propensity to make indulgent (vs. virtuous) food choices is moderated by their healthy eating concerns. Our findings revealed a weak but significant association between participants' self-reported hunger levels and their likelihood of making indulgent rather than virtuous food choices (e.g., preferring a chocolate cake instead of a fruit salad). Importantly, this effect was moderated by their healthy eating concerns, such that the link between hunger and choice likelihood of indulgent food options only emerged among participants who scored lower, but not higher, in healthy eating concerns. We also replicated these results in a robustness check that focused on the extent to which participants indicated having a healthy lifestyle (e.g., exercising regularly), with a similar moderating influence of this factor. Together, these findings shed light on the importance of considering certain boundary conditions for establishing a link between hunger and consumers' food choices, thus adding nuance to the growing body of hungerrelated literature. The results emphasize the importance of ensuring the availability of healthier snack options in environments wherein foods and beverages can be consumed, particularly at times when consumers tend to be hungry, to promote healthier eating habits.